2015
DOI: 10.1016/j.jconrel.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells affect the margination of microparticles in synthetic microcapillaries and intravital microcirculation as a function of their size and shape

Abstract: A key step in particle-based drug delivery throughmicrocirculation is particlemigration from blood flow to vesselwalls, also known as “margination”,which promotes particle contact and adhesion to the vesselwall. Margination and adhesion should be independently addressed as two distinct phenomena, considering that the former is a fundamental prerequisite to achieve particle adhesion and subsequent extravasation. Although margination has beenmodeled by numerical simulations and investigated inmodel systems in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 67 publications
2
69
0
Order By: Relevance
“…However, margination is not limited to WBCs and has been observed for other particles as well (2). This has sparked a lot of interest because of its potential applications in relation to cancer therapy (3)(4)(5)(6)(7). Tumor sites are generally characterized by 1) leaky vasculature, which allows drugcarrying particles to diffuse into them, and 2) a lack of lymphatics, which allows these particles to remain inside the tumor.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, margination is not limited to WBCs and has been observed for other particles as well (2). This has sparked a lot of interest because of its potential applications in relation to cancer therapy (3)(4)(5)(6)(7). Tumor sites are generally characterized by 1) leaky vasculature, which allows drugcarrying particles to diffuse into them, and 2) a lack of lymphatics, which allows these particles to remain inside the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…This so-called enhanced permeability and retention effect (8) further opens up the possibility of delivering chemotherapeutic drugs passively and more specifically to tumor sites, thereby limiting any damage to healthy tissues (9,10). A number of recent experimental (3,7,(11)(12)(13)(14)(15)(16)(17) and theoretical (18)(19)(20)(21)(22)(23) studies have suggested that particles of certain sizes and shapes have a higher margination propensity. This would facilitate the diffusion of these particles into tumor sites by allowing them to reach the leaky blood vessel walls and, ultimately, the tumors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, imaging has shown how red blood cells influence nano- and micro-particle margination in flow through capillary beds [35], which is more pronounced for larger (>100 nm) particles [46] compared to smaller NPs. Such margination impacts fluid mechanics and stresses experienced by the particles, is a function of both NP size and shape, and may actually be beneficial for extravasation at target sites [35]. IVM furthermore supports measurement of NP aggregation and clotting processes, especially as they occur in microvasculature, for instance as was seen with cationic siRNA-loaded hydrogel NPs [155].…”
Section: The Nuts and Bolts Of Ivm Nanoparticle Imagingmentioning
confidence: 99%